Like fire in the bones : listening for the prophetic word in Jeremiah - Brueggemann, Walter (Fortress Press, 2006)
This work features landmark essays on the prophet Jeremiah. It helps readers hear Jeremiah's voice as an important message for today. Topics examined include: Jeremiah's use of rhetorical questions; theology in Jeremiah; next steps in Jeremiah studies; when Jerusalem gloats over Shiloh; and a second reading of Jeremiah after the dismantling. The book is written by a highly respected Old Testament scholar and bestselling author.